2013
DOI: 10.1371/journal.ppat.1003213
|View full text |Cite
|
Sign up to set email alerts
|

An Overexpression Screen of Toxoplasma gondii Rab-GTPases Reveals Distinct Transport Routes to the Micronemes

Abstract: The basic organisation of the endomembrane system is conserved in all eukaryotes and comparative genome analyses provides compelling evidence that the endomembrane system of the last common eukaryotic ancestor (LCEA) is complex with many genes required for regulated traffic being present. Although apicomplexan parasites, causative agents of severe human and animal diseases, appear to have only a basic set of trafficking factors such as Rab-GTPases, they evolved unique secretory organelles (micronemes, rhoptrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
236
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(248 citation statements)
references
References 68 publications
12
236
0
Order By: Relevance
“…The two groups of genes were clearly segregated on the basis of their phenotype scores ( p = 6.7 × 10 −16 ), with lower scores for the essential genes (Figure 3D). The most prominent outlier was RAB4 , which appeared to be essential based on overexpression of a dominant-negative allele (Kremer et al, 2013). However, we readily obtained RAB4 knockouts that grew normally (Figure S1), demonstrating its dispensability in cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…The two groups of genes were clearly segregated on the basis of their phenotype scores ( p = 6.7 × 10 −16 ), with lower scores for the essential genes (Figure 3D). The most prominent outlier was RAB4 , which appeared to be essential based on overexpression of a dominant-negative allele (Kremer et al, 2013). However, we readily obtained RAB4 knockouts that grew normally (Figure S1), demonstrating its dispensability in cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular and molecular mechanisms underlying rhoptry biogenesis, including their targeting to the apical pole, are currently not well understood. Previous studies have, however, shown that perturbation of T. gondii proteins involved in vesicular trafficking, such as the dynamin-related protein B (DrpB), sortilin-like receptor (SORTLR), clathrin heavy chain 1 (CHC1) or the RabGTPases Rab5A and Rab5C result either in a block of both rhoptry and microneme biogenesis and/or in mistargeting of the proteins to either of the two organelles (Breinich et al, 2009;Kremer et al, 2013;Pieperhoff et al, 2013;Sloves et al, 2012). The T. gondii armadillo repeats only protein (ARO) is a key factor ensuring the apical distribution of rhoptries (Beck et al, 2013;Mueller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Though numerous studies to date have implicated the role of various trafficking components in trafficking to the apical organelles, including dynamin-like proteins [8], Rabs [9], and trans-membrane cargo receptors [10], much remains to be deciphered about these critical processes. One of the main questions is how post-Golgi cargo sorting and coat recruitment are involved in the specificity of trafficking to the rhoptries, and distinct sub-populations of micronemes.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation of DrpB in T. gondii results in the absence of distinct micronemes and rhoptries [8]. Rab GTPases, specifically Rab5a and 5c, are involved in targeting at least a subset of micronemal and rhoptry proteins [9]. Additionally, for soluble rhoptry and microneme contents, transmembrane receptors such as TgSORTLR are required for appropriate targeting [10].…”
Section: Introductionmentioning
confidence: 99%